Wave induced stress profile on a paired column semisubmersible hull formation for column reinforcement. (15th July 2017) - Odijie, Agbomerie Charles; Quayle, Stephen; Ye, Jianqiao
Highlights: Hydrodynamic loading effects on the columns of a paired-column semi-submersible was investigated. Modelling technique adopted for the fluid-structure interaction problem is well described. Stress distribution around the columns due to varying wave amplitudes and flow orientations are provided. Areas within the columns of the PC-Semi that may require additional reinforcement are identified. Abstract: A study into reinforcing the hull of the recently developed paired column semisubmersible platform has been carried out by understanding the stress profile around its columns from hydrodynamic interaction during survival and extreme weather conditions in the Gulf of Mexico. The conceptualization of this hull system is to enable dry-tree technology on semisubmersibles for deep-sea exploration. Its hydrodynamic response behaviour has been confirmed to be compatible with this technology, although its size and high steel requirement are of major disadvantage. Preliminary CFD study has showed an unusual flow behaviour within and around the hull due to its unique column arrangement. This behaviour creates an unusual hydrodynamic pressure profile on the hull, dominated by the wave parameters. Numerical models were developed using ANSYS and AQWA to compute the stress distribution on the columns from this unique uneven hydrodynamic pressure. The boundary conditions for the FE-model were formulated using hydrostatic stiffness theories and hydrodynamic response plots developed in Orcaflex. The results have showed high stress concentration on the inner columns. For operating conditions (low wave amplitude), the wave propagating direction was observed to have little or no effect on the column stress distribution. Significant effect of the wave propagating angle was observed as its amplitude gradually increases. Results for topside and deck mass effect on the stress distribution on the columns also suggested high stress distribution around the joint area of the inner columns for extreme and survival weather conditions, irrespective of the flow orientation.